Traumatic Stress and Pediatric Pain: Towards a Neurobiological Stress-Health Perspective - Kao, Grace S. (J Child Adolesc Trauma, 2017)
This theoretical review aims to present the limited findings on traumatic stress and pain in children and adolescents, highlight recent discoveries regarding neurobiological processes, and suggest an alternative stress-health perspective in the future study and conceptualization of pediatric pain and traumatic stress based on results. Current literature highlights a positive correlation between pain and trauma symptoms in youth and suggests a complex relationship that may have mutually maintaining dynamics and intertwined physiological processes. Developmentally sensitive, longitudinal, process-oriented designs assessing neurobiological alterations and stress responses should be utilized in the examination of the trauma-pain relationship. Such investigations may provide a more unified explanation of the relationship between chronic pain and traumatic stress.